Genetic testing of newborns for type 1 diabetes susceptibility: a prospective cohort study on effects on maternal mental health - Magnus Per; Kise Marit S; Tambs Kristian; Aas Kaja K; Rønningen Kjersti S (BMC, 2010)
Abstract Background Concerns about the general psychological impact of genetic testing have been raised. In the Environmental Triggers of Type 1 Diabetes (MIDIA) study, genetic testing was performed for HLA-conferred type 1 diabetes susceptibility among Norwegian newborns. The present study assessed whether mothers of children who test positively suffer from poorer mental health and well-being after receiving genetic risk information about their children. Methods The study was based on questionnaire data from the Norwegian Mother and Child Cohort (MoBa) study conducted by the Norwegian Institute of Public Health. Many of the mothers in the MoBa study also took part in the MIDIA study, in which their newborn children were tested for HLA-conferred genetic susceptibility for type 1 diabetes. We used MoBa questionnaire data from the 30th week of pregnancy (baseline) and 6 months post-partum (3-3.5 months after disclosure of test results). We measured maternal symptoms of anxiety and depression (SCL-8), maternal self-esteem (RSES), and satisfaction with life (SWLS). The mothers also reported whether they were seriously worried about their child 6 months post-partum. We compared questionnaire data from mothers who had received information about having a newborn with high genetic risk for type 1 diabetes (N = 166) with data from mothers who were informed that their baby did not have a high-risk genotype (N = 7224). The association between genetic risk information and maternal mental health was analysed using multiple linear regression analysis, controlling for baseline mental health scores. Results Information on genetic risk in newborns was found to have no significant impact on maternal symptoms of anxiety and depression (p = 0.9), self-esteem (p = 0.2), satisfaction with life (p = 0.2), or serious worry about their child (OR = 0.98, 95% CI 0.64-1.48). Mental health before birth was strongly associated with mental health after birth. In addition, an increased risk of maternal worry was found if the mother herself had type 1 diabetes (OR = 2.39, 95% CI 1.2-4.78). Conclusions This study did not find evidence supporting the notion that genetic risk information about newborns has a negative impact on the mental health of Norwegian mothers.